An empirical investigation of determinants for adoption of C2C auction marketplaces. (11th May 2022) - Chauhan, Sumedha; Goyal, Sandeep; Gupta, Parul; Jaiswal, Mahadeo; Mehta, Nikhil
In the last two decades, online and real-time interactions have grown significantly between individual buyers and sellers. Consumer-to-consumer (C2C) electronic-commerce (e-commerce) has been increasingly adopted by the people as a direct interface for buying and selling products or services. This research focuses on identifying the key determinants for adoption of C2C auction marketplaces, especially online auctions. Rogers' (2003) diffusion of innovation (DoI) theory has been used as the guiding framework for this study as C2C e-commerce falls into the category of technological innovation. Research methodology involves quantitative survey of 278 consumers of C2C auction marketplace in India and the application of logistic regression to determine the impact of DoI attributes on C2C e-commerce adoption. Research findings indicate that relative advantage, observability, perceived security, age, and gender influence the adoption of C2C auction marketplaces. However, compatibility, complexity, and trialability do not significantly influence the adoption of C2C auction market places.